The experiences of Bidayuh in the development of Native Customary Rights LAND in Singai / John Jussem, Nero Madi and Patrick Atan - Jussem, John; Madi, Nero; Atan, Patrick (Faculty of Administrative Science and Policy Studies, 2012)
The objectives of this study are twofold. Firstly, the study identifies locally specific native customary land tenure in Singai, Sarawak. Secondly, based on this land tenure system, the study examines how the natives respond to land development policies. This paper discusses the Bidayuh concept of native customary land tenure and how the concept is being used to reject state initiated NCR land developments. Methodology of this study was done in a qualitative and quantitative manner whereby structured questionnaires coupled with interviews were conducted. Literature review and secondary data were also employed. Data, analysis was done using the SPSS software (version 17) by applying descriptive statistic as well as drawing findings from empirical evidences. The findings, among others, suggest that native customary rights land in Singai has been preserved by the practise of traditional land tenure. The native customary rights to land covers what the natives themselves refer to as damun, obut, purau. Their perseverance to practise their native customary rights on their NCR lands has seen many of them rejecting often used model of NCR land development, preferring instead to an alternative method of self development. This alternative method has also spawned a community based organisation called REDEEMS (Research and Development Movement of Singai) which the native Singai hoped to use in order to ride the waves of unpredictable development for the future. The finding is pertinent as it will shed some light to the relevant authorities and other ethnic native group on how to avoid conflicts and at the same time to assert their native customary rights to land.